WATER CONDITIONS OF CORAL REEFS WITH FORAMINIFERA BENTHIC AS BIOINDICATOR BASED FORAM INDEX IN BANGGAI ISLANDS, PROVINCE OF CENTRAL SULAWESI - Khairunisa N. Aulia; Hikmat Kasmara; Tatang S. Erawan; Suhartati M. Natsir (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
Research of water condition of coral reefs with foraminifera benthic as bioindicator based on FORAM Index (FI) in Banggai Islands, Province of Central Sulawesi was conducted by P2O-LIPI, Jakarta team in July 2011.  This study was an exploratory research, conducted using survey methods. Sediment sampling was collected by a Van Veen Grab and measurement of other biotic and abiotic parameters was performed in 8 point sampling stations scattered in Banggai islands. Sediment samples were analyzed qualitatively and quantitatively to identify the types of foraminifera, determines FORAM Index, and find out  the relationship between FORAM Index with condition of coral reefs views by coral cover. The results showed that foraminifera benthonic as bioindicator were 75 species, which belong to  33 genera. Water conditions of Banggai Islands by FORAM Index (FI) values ​​ranged from 2.99 to 5.54. There was a fairly close relationship between FI with condition of coral reefs views by percentage coral cover in Banggai Islands. Keywords : coral reefs, FORAM Index, foraminifera benthic, Banggai Islands